Effectiveness and safety of bedaquiline-containing regimens in the treatment of MDR- and XDR-TB: a multicentre study - Borisov, Sergey E; Dheda, Keertan; Enwerem, Martin; Romero Leyet, Rodolfo; D'Ambrosio, Lia; Centis, Rosella; Sotgiu, Giovanni; Tiberi, Simon; Alffenaar, Jan-Willem; Maryandyshev, Andrey; Belilovski, Evgeny; Ganatra, Shashank; et al. (The European respiratory journal, 2017)
Large studies on bedaquiline used to treat multidrug-resistant (MDR-) and extensively drug-resistant tuberculosis (XDR-TB) are lacking. This study aimed to evaluate the safety and effectiveness of bedaquiline-containing regimens in a large, retrospective, observational study conducted in 25 centres and 15 countries in five continents.428 culture-confirmed MDR-TB cases were analysed (61.5% male; 22.1% HIV-positive, 45.6% XDR-TB). MDR-TB cases were admitted to hospital for a median (interquartile range (IQR)) 179 (92-280) days and exposed to bedaquiline for 168 (86-180) days. Treatment regimens included, among others, linezolid, moxifloxacin, clofazimine and carbapenems (82.0%, 58.4%, 52.6% and 15.3% of cases, respectively).Sputum smear and culture conversion rates in MDR-TB cases were 63.6% and 30.1%, respectively at 30 days, 81.1% and 56.7%, respectively at 60 days; 85.5% and 80.5%, respectively at 90 days and 88.7% and 91.2%, respectively at the end of treatment. The median (IQR) time to smear and culture conversion was 34 (30-60) days and 60 (33-90) days. Out of 247 culture-confirmed MDR-TB cases completing treatment, 71.3% achieved success (62.4% cured; 8.9% completed treatment), 13.4% died, 7.3% defaulted and 7.7% failed. Bedaquiline was interrupted due to adverse events in 5.8% of cases. A single case died, having electrocardiographic abnormalities that were probably non-bedaquiline related.Bedaquiline-containing regimens achieved high conversion and success rates under different nonexperimental conditions.